2005
DOI: 10.1002/mrm.20455
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of single human carcinoma cells in vitro using a clinical whole‐body magnetic resonance scanner at 3.0 T

Abstract: The purpose of the present study was to examine whether single human carcinoma cells labeled with iron oxide nanoparticles could be detected by magnetic resonance (MR) imaging on a clinical 3-T scanner using a surface coil only. WiDr human colon carcinoma cells were loaded with two kinds of iron oxide nanoparticles differing by coating and size: aminosilan-coated (MagForce) and carboxy-dextran-coated particles (Resovist). The latter were preferred by the colon carcinoma cell line used here and taken up much fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…Subsequently, we performed small animal PET followed by MR imaging and we were able to noninvasively detect our particles basically in the liver and spleen with both modalities. It is well known that iron oxide accumulates during first pass in the reticuloendothelial system of the liver and the spleen [12,13]. Enabled by the added FITC, fluorescence microscopy revealed the histological affirmation.…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, we performed small animal PET followed by MR imaging and we were able to noninvasively detect our particles basically in the liver and spleen with both modalities. It is well known that iron oxide accumulates during first pass in the reticuloendothelial system of the liver and the spleen [12,13]. Enabled by the added FITC, fluorescence microscopy revealed the histological affirmation.…”
Section: Discussionmentioning
confidence: 79%
“…Several groups [13][14][15][16][17] have reported the detection of single SPIO labeled cells by means of R * 2 relaxation rate enhancement as measured with gradient echo sequences. We showed that a concentration of a single SPIO labeled cell (20 pg Fe/cell) per MR imaging voxel of 1 µl causes significant reductions in the gradient echo signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-directed imaging of magnetically labeled cell has also been under experimental study [6]. Even the detection of single labeled cells has been reported [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…Pinkernelle and colleagues (2005) reported that single IO nanoparticlelabeled human colon carcinoma cells can be detected using MRI techniques in vitro, the lowest concentration of iron needed is about 4-5 μg/10 6 cells (Pinkernelle et al 2005). For imaging by targeted IO nanoparticles, the sensitivity depends on the target concentrations in tumor cells, for example, some targets are often quite weakly expressed (10 4 folate receptors in brain glioma cells) (Saul et al 2003) while others are very highly expressed (3 × 10 6 epidermal growth factor receptors in A431 human squamous carcinoma cells) (Jinno et al 1996).…”
Section: Targeted Io Nanoparticles For Tumor Imagingmentioning
confidence: 99%